Circulating Tumor DNA Testing Supports Rapid Therapeutic Decision-Making in Metastatic Melanoma: A Case Report - Behera, Tapas Ranjan; Song, Jung Min; Ko, Jennifer; Eicher, Donald; Arbesman, Joshua; Gastman, Brian; Farkas, Daniel H.; Funchain, Pauline (Frontiers in Oncology, 2022)
Treatment of metastatic melanoma includes the option of targeted therapy in patients with driver BRAF mutations. BRAF-MEK inhibitor drugs improve survival in the approximately 50% of patients with melanoma that harbor BRAF mutations. As BRAF mutation detection in tissue often takes days to weeks, it is not always possible or timely to obtain BRAF status in tissue using immunohistochemistry or next generation sequencing. Plasma-derived circulating tumor DNA (ctDNA) is a potential alternative analyte in such treatment settings. We present a case of metastatic melanoma that was treated in an emergent setting using therapy supported by rapid PCR-based detection of ctDNA positive for a BRAF V600 mutation. In this rapidly deteriorating 53-year-old male with diffuse melanoma metastases and unknown BRAF mutation status requiring hospital admission, a plasma-based BRAF mutation detection supported treatment with targeted therapy, dabrafenib and trametinib. Same-day initiation of therapy resulted in swift amelioration allowing discharge within a week, followed by substantial clinical improvement over the following weeks. In cases requiring urgent clinical decision making, a plasma-based, near point-of-care detection system is useful in supporting targeted therapy decisions without the need for invasive and time-consuming biopsy.